BISNIS KESEHATAN BERBASIS DIGITAL: INTENSI PENGGUNA APLIKASI DIGITAL HALODOC - Indriyarti, Eko Retno; Wibowo, Suryo (Universitas Bunda Mulia, 2020)
Everybody needs continuous health both in normal conditions and in pandemic conditions like this time. Digital-based health services are present in the community to meet existing needs. The community as users is faced with a variety of health service choices according to user preferences and needs. The public in general has known about digital-based health services but have not used them because they have considerations, namely price. On the other hand, people who have used it are more concerned about the benefits and ease of using these digital health services. This study aims to explain the influence of Perceived Usefulness and Perceived Ease of Use on Intention of using Halodoc digital health services in Jakarta. The sample in this study were 135 people. Using multiple regression analysis with SPSS 25.0, the results of this study explain that partially and simultaneously the intention to use Halodoc is influenced by the factors of Perceived Usefulness and Perceived Ease of Use. During difficult times due to this pandemic, it is hoped that the next research will use related external factors such as environmental / social factors and employment status or income.